Integrating Big Data and Information Systems in Higher Education: Implications for Organizational Productivity and Efficiency - Yulis Nuryanti; Yosua Novembrianto Simorangkir; Masduki Asbari; Yusriel Arief Ferdiyanto; Hatoli Waruwu (Yayasan Aya Sophia Indonesia, 2025)
The digital transformation of higher education has accelerated the adoption of big data and integrated information systems, reshaping institutional governance, academic performance monitoring, and strategic decision-making. Despite the proliferation of digital platforms, many institutions continue to operate within fragmented data environments, limiting their capacity for organizational productivity and efficiency. This study explores how the integration of big data and information systems contributes to institutional performance enhancement in higher education. Employing a qualitative descriptive methodology, data were collected through semi-structured interviews, document analysis, and direct observations across selected Indonesian universities. The findings reveal that successful integration models—characterized by strategic alignment, leadership commitment, and cross-functional collaboration—lead to improved decision-making, resource optimization, and streamlined workflows. Conversely, challenges such as data silos, resistance to change, and technical limitations hinder implementation. The study also reflects on the integration through the lens of Resource-Based View (RBV) and Socio-Technical Systems Theory, emphasizing the need for holistic and adaptive approaches. Recommendations include the development of strategic roadmaps, robust data governance, and inclusive capacity-building initiatives. This research contributes to the global discourse on digital transformation in higher education, offering practical insights for institutional leaders and policymakers seeking to enhance organizational resilience and responsiveness through data-driven innovation.